2012
DOI: 10.1100/2012/603539
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Body Acupuncture on Obesity: Anthropometric Parameters, Lipid Profile, and Inflammatory and Immunologic Markers

Abstract: A randomized controlled clinical trial in 196 obese subjects was performed to examine the effectiveness of body acupuncture on body weight loss, lipid profile and immunogenic and inflammatory markers. Subjects received authentic (cases) or sham (controls) acupuncture for 6 weeks in combination with a low-calorie diet. In the following 6 weeks, they received the low-calorie diet alone. Subjects were assessed at the beginning, 6 and 12 weeks later. Heat shock protein (Hsps)-27, 60, 65, 70 antibody titers and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 33 publications
5
63
2
Order By: Relevance
“…Significant decreases in total cholesterol, 66 76 LDL-C 76 85 and triglycerides 66 76 were observed whereas HDL-C did not change significantly. 76 In another study 84 there were significant decreases in lipoprotein A and apolipoprotein B and no changes in apolipoprotein A levels.…”
Section: Effects On Lipid Metabolismmentioning
confidence: 91%
See 2 more Smart Citations
“…Significant decreases in total cholesterol, 66 76 LDL-C 76 85 and triglycerides 66 76 were observed whereas HDL-C did not change significantly. 76 In another study 84 there were significant decreases in lipoprotein A and apolipoprotein B and no changes in apolipoprotein A levels.…”
Section: Effects On Lipid Metabolismmentioning
confidence: 91%
“…For EA the evidence is more positive; the majority of studies suggest that EA induces significantly greater weight loss than sham EA, 18 78 or acupuncture performed at no acupuncture points 85 whereas only one study concluded that EA and exercise resulted in similar reductions in body weight. 77 Effects on obesity-related peptides As already mentioned, obesity is characterised by hyperleptinaemia and leptin resistance.…”
Section: Effect Of Different Types Of Acupuncture On Body Weight Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Li and Wang [16], from China also have reported significant changes in total and LDL cholesterol during acupuncture therapy. In Iran, Abdi et al [3], studied the weight loss of 196 subjects and stated that acupuncture intervention was associated with improvement in lipid profile with significant difference in TC, LDL-C, but not significant difference in fat %. However, some studies in agree with current lipid profile but with no changes for HDL-C as Cabioglu and Ergene [17] when studied obese women from Turkey and Sun and Xu [18] who studied obese patients from Chongqing in China, this may be explained by application of different acupoints.…”
Section: Discussionmentioning
confidence: 99%
“…Several weight loss strategies have been developed and experimented over the past decades for treatment of obesity in order to improve health [3]. Common intervention methods for obesity include lowcalorie diet, exercise.…”
Section: Introductionmentioning
confidence: 99%